Gender violence in Australia: historical perspectives - Piper, Alana; Stevenson, Ana (Australian history, 2019)
Historicising a "national disgrace": towards a feminist history of domestic violence since 1788 / Zora Simic -- Discovering violence in the family / Tanya Evans -- Understanding economic abuse as domestic violence / Alana Piper -- "Your troubles are over, Mummy": prosecuting children who kill violent men / Lisa Durnian -- Uncovering a hidden offence: social and legal histories of familial sexual abuse / Andy Kaladelfos -- Criminalizing the husband and the home: marital rape law reform, 1976-1994 / Lisa Featherstone -- The "drover's boy" and indigenous women's unthinkable consent / Liz Conor -- Sex trafficking, labour migration, and the state / Rae Frances -- Gender-based violence in out-of-home care / Shurlee Swain -- "It was quite a scary time": lesbians and violence in post-war Australia / Rebecca Jennings -- "Laying siege and storming citadels": hostility and marginalisation in higher education / Tanya Fitzgerald -- From page to meme: the print and digital revolutions against gender violence / Ana Stevenson and Brigitte Lewis -- Feminist films on women's experiences of violence / Mary Tomsic -- Domestic violence activism in Victoria, 1974-2016 / Jacqui Theobold and Suellen Murray.